Basic characteristics of wireless power transfer - Abdul Shukor, Fairul Azhar; Mohd Nasir, Nur Ashikin; Aris Fazil, Aris Luqmanul Hakim; Raja Othman, Raja Nor Firdaus Kashfi (School of Engineering, Taylor’s University, 2019)
Nowadays, wireless power transfer had been used in many applications such as the mobile phone and Electric Vehicle (EV) charging. This paper presented an idea that is discussed a concept of wireless power transfer. The basic design, merits, and demerits, applications of wireless power transfer are also discussed. Through laboratory experiment testing, data is collected and analysed. Construction of a prototype and the complete schematic of the prototype is presented in this paper. The performance of the WPT is analysed. The experiment starting with the hardware fabrication of the WPT module and the single-phase inverter. By proceeding with measurement of a characteristic of the WPT, which are the resistance (R), inductance (L), voltages (V) current (I) and power (P); some experiments were done to get expected results, which meet the objectives of the project